Health risk behaviours among adolescents in Argentina: trends between 2007, 2012 and 2018 national cross-sectional school surveys - Karl Peltzer; Supa Pengpid (BMC, 2021)
Abstract Background The aim of this study was to assess trends of various health risk behaviours among adolescents across three different surveys in Argentina. Methods Data from 115,697 adolescents (mean age:14.6 years, SD=1.2) that participated in three cross-sectional national school surveys in 2007, 2012 and 2018 were analysed. In all, 27 health risk behaviours were assessed through a self-administered questionnaire. Significance of a linear trend was tested by treating study year as categorical variable in logistic regression analyses, adjusted by age group and food insecurity for boys and girls separately Results Among both sexes, four health risk behaviours (current cigarette use, passive smoking, trouble from alcohol use, and physically attacked) significantly reduced from 2007 to 2018. Among boys five health risk behaviours (experience of hunger, parental tobacco use, current alcohol use, involvement in physical fighting, and multiple sexual partners), and among girls, inadequate physical activity significantly reduced over time. Among both sexes, the prevalence of four health risk behaviours (overweight/obesity, obesity, leisure-time sedentary behaviour and insufficient fruit intake) significantly increased among both sexes, and among girls ten health risk behaviours (not walking/biking to school, current other tobacco use, bullying victimisation, lifetime drunkenness, having no close friends, suicide plan, suicidal ideation, worry-induced sleep disturbance, loneliness, and ever sexual intercourse) significantly increased over time. Conclusion Nine health risk behaviours among boys and five health risk behaviours among girls decreased, and four health risk behaviours among boys and 14 health compromising behaviours among girls increased over a period of 11 years. School health programmes for adolescents should be strengthened in Argentina.